Theodore the Studite and his opposition to imperial power: an analysis of the Moechian Controversy and the Second Iconoclasm - Fernandes, Caroline Coelho (Romanitas - Revista de Estudos Grecolatinos, 2021)
Theodore the Studite was a monk who, in the course of the 9th century, was an important force of opposition to imperial decisions judged by him as outrageous to Byzantine Christian ideals. On two occasions he was opposed to the emperor and his actions, suffering consequences and punishments, such as exile. As a result, our objective is part of the attempt of understanding Theodoro's role as an agent of opposition to the Imperial Palace and its relations with it, since the monks were considered important means of contact and influence on Byzantine society. We intend to do this from the case study of the Moechian Controversy and the Second Iconoclasm (815-843), where in both the monk was the protagonist.
Keywords: Theodore the Studite; Moechian Controversy; Iconoclasm; Imperial Power; Byzantium